(untitled) (Nóema, 2014)
I. Kant’s Critique of Judgment is a maintext to catch the epistemological tensions created by the emerging notion of life. By investigating the specific causality of life in order to explain the phenomenon of self-organization of the living, Kant uses the remarkable concept of technique of nature, thus establishing a strong analogy between technique and life.The consequences of this analogy affect not only the epistemology of life, but also the modern conception of technique.To a technicization of life corresponds a vitalization of technique. A new hybrid territory is thus discovered – that of technical life – in whichstands the possibility of a biological archaeology of modern technique.